The Impact of Village Financial Systems and Staff Competence on Village Financial Report Quality: The Role of Fraud Prevention as a Mediator - Hamisi, Astrid Ivo; Sirat, Abdul Hadi; Hadady, Hartati (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This research aims to examine how village financial systems and staff competence impact the quality of village financial reports, with fraud prevention playing a key role. This study is crucial for promoting transparency and accountability in village financial management. Using path modeling with smart partial least squares (PLS), the study reveals important findings. Village financial systems and staff competence do not directly influence the quality of financial reports significantly. However, both factors have a significant impact on fraud prevention. This research is urgent because it addresses the critical need to ensure trustworthy financial reporting by village administrations. The findings underscore the importance of effective strategies for managing financial risks at the village level. Moreover, the study demonstrates that village financial systems and staff competence significantly influence financial report quality through their effects on fraud prevention. Conducted in the South and North Morotai Districts, Pulau Morotai Regency, this study aims to contribute positively to enhancing the efficiency and transparency of village financial governance.